Assessing the Relationship between Short Birth-to-Pregnancy Interval and the Maternal and Perinatal Outcomes among Multiparous Women in Northern Ghana - Agulu, Gilbert G.; Dzotsi, Emmanuel K.; Issah, Kofi; Nyuzaghl, Josephat A.; Adogboba, Alemna D.; Adongo, Vincent A. (European Scientific Journal, ESJ, 2024)
Introduction: The World Health Organization (WHO) recommends an optimal Birth-to-Pregnancy Interval (BPI) of 24-59 months, or a 33-month interval between two successive births to reduce the risk of untoward maternal and newborn outcomes. Short Birth to Pregnancy Interval (SBPI), and unmet need for Family Planning (FP) are the major contributors to rapid population growth and increased maternal and newborn mortalities. The purpose of this study was to assess the adverse perinatal and maternal outcomes associated with SBPI among multiparous women in three municipalities of the Upper East Region (UER) of Ghana. Materials and Methods:The study employed the Cross-sectional Design conducted among 904 women aged 15-49 years attending Antenatal Care (ANC) clinics in three municipalities in the UER who had at least two successive live births prior to data collection. Data was collected using structured questionnaire, incorporated into the electronic data collection tool, Kobo collect and administered by trained research assistants. Birth interval was categorized according to the WHO’s classification, <24 months as SBPI, 24-≥59 months as Optimal Birth to Pregnancy Interval (OBPI) and >59 months as Long Birth to Pregnancy Interval (LBPI). Results: Of the 904 respondents, the majority (56.2%) had an OBPI, while 36.9% had a SBPI. Factors that influenced SBPI were parity, mode of delivery, and the educational status of women’s partner. Participants with a higher parity (≥5 children) had 0.67 times the potential of spacing their births (AOR 0.67; 95% CI 0.46-0.98; p = 0.040). Women who experienced a Caesarean Section (CS) delivery were 3.28 times more likely to have LBPI (AOR 3.28; 95% CI 1.02-10.62; p=0.047). Respondents whose partners had secondary education had a 1.87 chance (AOR 2.07; 95% CI 1.09-3.96; p=0.027) of spacing their births. The birth complications reported were retained products of conception (41.9%), pregnancy-induced hypertension (27.9%), postpartum hemorrhage (11.6%), obstructed labor (10.5%), sepsis (38.1%), neonatal jaundice (23.8%), low-birth-weight (19%), and preterm birth (14.3%). Conclusion and Global Health Implications: The study recommends health professionals in direct contact with maternal, reproductive, and child health to be proactive in FP counseling, and to support women decision making.